Application of transesophageal echocardiography combined with FloTrac monitoring in cardiac valve replacement surgery - Li, Yunpeng; Liu, Ying; Zhang, Dandan (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo compare intraoperative hemodynamics between transesophageal echocardiography (TEE) combined with FloTrac vs. TEE with invasive arterial pressure monitoring, and to examine associations with postoperative cognitive dysfunction (POCD) in patients undergoing cardiac valve replacement.MethodsA retrospective matched-cohort study included 162 patients (81 per group) matched by surgical type, ASA classification, age, and cardiopulmonary bypass time. Hemodynamic parameters were measured at four time points (T1–T4). Linear mixed-effects models assessed group, time, and interaction effects. Exploratory logistic regression preserving the matched design evaluated associations with POCD.ResultsGroup effects were significant for heart rate (HR, F = 6.79, p = 0.009), cardiac output (CO, F = 17.05, p < 0.001), cardiac index (CI, F = 16.49, p < 0.001), and stroke volume variation (SVV, F = 18.73, p < 0.001). Group × time interactions were observed for MAP, CVP, HR, SV, CI, SVRI, SVV, VTI, and LVEDV (all p < 0.05). Pearson correlations at T3 were weak (SV vs. CI r = 0.274; FAC vs. SVRI r = −0.220). Postoperative complication rates, including POCD (9.9% vs. 18.5%, OR = 0.48, 95% CI: 0.19–1.21, p = 0.115), were not significantly different. HR at T2 and SVRI at T4 showed nominal associations with POCD, but predictive ability was limited.ConclusionTEE combined with FloTrac provides a more detailed intraoperative hemodynamic assessment and reveals distinct temporal trends compared to invasive arterial pressure monitoring. These differences did not correspond to changes in clinical outcomes in this cohort, but the observations may inform the design of future studies on hemodynamic monitoring strategies and POCD risk.